Upaya Guru Pendidikan Agama Kristen dalam Pembentukan Karakter Siswa Menghadapi Tantangan Masa Depan - Ohoitimur, Hendrica Henny; Douw, Devita; Natalia, Desi (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2023)
The objectives to be achieved in the research of this scientific work are to determine the influence of lack of Christian Religious Education on character building, the influence of Christian Religious Education on Christian students, and the level of influence of Christian Religious Education on the character building of Christian Students at SD Inpres Pos 7 Sentani. The research method used in this study is Classroom Action Research. It was found that students who study PAK at SD Inpres Pos 7 Sentani, especially in grades IV-V, are formed by having Christian character seen from three indicators, namely indicators similar to Christ, quality of life, and responsibility, where these indicators complement each other and cannot be separated from one another. All of these indicators must be practiced by students in a balanced manner in following the PAK learning process so that they become Christian character builders that can be owned. Students with Christian character cannot be separated from PAK learning and this has a positive relationship. This is evidenced by the analysis of the research results which reached 45% of students who gave a high response. Through the results of this PTK, it can be concluded that there are still some students who have not displayed Christian character optimally in the PAK learning process. This is evidenced by the analysis of the research results which reached 23.61% of students who gave a low response.